Statistical Evaluation of Indoor Air Quality Parameters in Classrooms of a University - Zeki Argunhan; Ali Serkan Avci (Advances in Meteorology)
This study was carried out in order to determine the indoor air quality of the classrooms existing in university (Turkey). Relative humidity, temperature, carbon dioxide, radon, and particulate matters (PM0.5, PM1.0, PM2.5, PM5.0, and PM10) were taken into account as the parameters of indoor air quality measurements. The results obtained from the present work were interpreted by comparing them with the standards of different countries. The relations between all parameters were statistically examined by means of correlation and regression analysis in SPSS 17 statistical program. As a result, it was observed that indoor temperature was lower than the standards, yet carbon dioxide and PM values were higher than the upper limit, but relative humidity level was within comfort conditions. The average indoor radon concentrations were found to be below the recommended reference levels for International Commission on Radiological Protection (ICRP), yet it was seen that the results were relatively higher in comparison with the worldwide values. In addition, it was determined that there was a meaningful relation between outdoor relative humidity, indoor relative humidity, and particulate matters in different diameters. Some solutions were suggested for the treatment of the indoor air quality for each parameter.